Manajemen Public Relations dalam Mengelola Reputasi pada Organisasi PERHUMAS - Achmad Rayhan; Nani Nurani Muksin (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study examines PERHUMAS's strategies in managing its reputation as a leading organization in public relations, amidst the dynamics brought by the emergence of the IPRA and PR Indonesia. Using a descriptive qualitative approach, the research relies on in-depth interviews and observations involving relevant informants. In the identification and planning phase, PERHUMAS utilizes social media, media monitoring, and media listening while collaborating with other parties. Their strategies are based on the organization's vision, mission, values, and code of ethics. Daily activities include routine monitoring, while long-term efforts position PERHUMAS as a benchmark for public relations practices and an educator for PR professionals. The action and communication phase involves programs such as national and international forums, accreditation, competency development, and positive image-building campaigns. PERHUMAS prioritizes transparent, structured, and sustainable communication. In the evaluation phase, the focus is on impact and feedback using the AMEC Integrated Evaluation Framework and Customer Satisfaction Index surveys. These results assist in measuring success and refining reputation management strategies.